Conductive carrier for electrocatalytic reduction of carbon dioxide, purification method and supported catalyst for electrocatalytic reduction of carbon dioxide

The described method for purifying conductive carriers through liquid-phase oxidation and dialysis in deionized water effectively addresses the inefficiencies in existing purification techniques, resulting in improved catalytic performance by reducing metal impurities and enhancing active site loading for CO2 electrochemical reduction.

CN119710778AInactive Publication Date: 2025-03-28PETROCHINA CO LTD

Patent Information

Application Number
CN202311274708.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing methods for purifying conductive carriers used in electrochemical reduction of CO2 are inefficient in removing impurities, leading to low utilization of active metal sites and poor catalytic performance due to the presence of metal ions and acid residues, which affects the loading and stability of catalysts.

Method used

A method involving liquid-phase oxidation of conductive carriers, followed by dialysis in deionized water to remove metal ions and acid residues, and subsequent washing with specific acid concentrations to enhance the purity and loading efficiency of the carriers, utilizing a concentration gradient for effective separation.

Benefits of technology

The method achieves a significant reduction in metal impurities, allowing for higher loading of active metal components and improved catalytic performance by releasing active sites on the conductive carriers, enhancing the electrochemical reduction of CO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004476584510000121
    Figure BDA0004476584510000121
  • Figure BDA0004476584510000131
    Figure BDA0004476584510000131
  • Figure HDA0004476584520000011
    Figure HDA0004476584520000011
Patent Text Reader

Abstract

The invention discloses a purification method of a conductive carrier for electrocatalytic reduction of carbon dioxide, which comprises the following steps: placing a conductive carrier crude product prepared by a liquid phase oxidation method in a dialysis bag, dialyzing in deionized water, and drying to obtain the conductive carrier for electrocatalytic reduction of carbon dioxide. According to the conductive carrier prepared by the preparation method, metal salts and anions on the surface of the carrier are removed through dialysis by adopting a dialysis bag, so that the obtained conductive carrier not only has a relatively large specific surface area and can load more metal active sites, but also can provide relatively high electron conduction efficiency; reducing the conduction resistance at the electrode-electrolyte interface; and during subsequent preparation of the catalyst, metal nanoparticles, especially copper-based nanoparticles, are easily loaded, so that the electrode catalyst for preparing ethylene through electrolytic reduction of carbon dioxide is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a conductive carrier and a purification method for electrocatalytic reduction of carbon dioxide, and a supported catalyst for electrocatalytic reduction of carbon dioxide. Background Art

[0002] With the rapid development of industry and the massive consumption of mineral fuels, the content of CO2 in the atmosphere has continued to grow over the past few decades, from 280ppm before the industrial revolution to the current 400ppm. From an economic point of view, due to its high functionality, rich, renewable carbon source, and environmental friendliness, carbon dioxide has become an important C1 raw material in organic synthesis. Therefore, how to convert carbon dioxide into liquid fuel or other useful chemicals, thereby achieving energy conservation and emission reduction, CO2 recycling and CO2 "zero emission" in a macro sense, has become a focus of attention. At present, the main ways to convert carbon dioxide into resources at home and abroad are biological conversion, photocatalytic conversion and electrochemical conversion.

[0003] Electrocatalysts are the key to achieving electrocatalytic reduction of carbon dioxide (electrochemical conversion). In order to achieve carbon-carbon coupling of carbon dioxide during electroreduction, copper-based nanoparticles are usually used as electrocatalysts. For example, Chinese patent document CN115490258A discloses a copper oxide nanosheet catalyst and its preparation method and its application in electrocatalytic reduction of carbon dioxide and carbon monoxide. A certain mass of copper salt is dissolved in water, an alkaline solution of a certain concentration is added, a certain volume of ethanol is added after stirring, and heated to a certain temperature for hydrothermal reaction. The copper oxide nanosheet is filtered and dried to obtain the copper oxide nanosheet, which is used for electrocatalytic reduction of carbon dioxide, carbon monoxide, or carbon monoxide / carbon dioxide co-electrolysis reaction, and the C-(2+) Faraday efficiency reaches more than 85%. However, the use of metal particles as catalysts for electrode forming loads may cause uneven dispersion of ink, resulting in metal particles stacking or metal particles vacancy after electrode forming, which easily leads to uneven current density of the electrode and poor electrode stability.

[0004] In response to this problem, researchers proposed to improve the conductivity of electrode catalysts by adding conductive carriers through physical mixing. For example, Chinese patent document CN115595607A discloses a composite catalyst and application for regulating the selectivity of carbon dioxide electrocatalytic reduction products. By adding carbon black to cuprous oxide micron particle catalysts to make composite electrocatalytic electrodes, the selectivity of carbon dioxide reduction products can be regulated from methane to ethylene. However, although the ink obtained by the above physical mixing improves the conductivity of the catalyst and reduces the cell pressure of the battery stack to a certain extent, since there is no loading relationship between the active component metallic copper and the carrier, the utilization rate of the catalyst metal sites by physical mixing is not high.

[0005] In response to this problem, Chinese patent document CN111659437A discloses a coated composite catalyst, specifically a method for preparing a nitrogen-doped graphene-supported core-shell copper-carbon Cu2O / Cu@C composite catalyst for electrocatalytic production of formic acid from carbon dioxide. However, the synthesis process of the coated structure catalyst itself is complicated. Therefore, the oxygen-containing functional groups originally carried on the carbon material can be used as targets for anchoring active metal components to load and synthesize the oxygen-containing carbon material conductive carrier, such as graphene oxide GO. For example, Chinese patent document CN113563759A discloses a composite material of graphene and nanosilver and a preparation method thereof, which controls the type and amount of oxygen-containing functional groups of graphene oxide and combines the reversible addition-fragmentation chain transfer (RAFT) polymerization technology to directionally and controllably graft oxygen-containing segments (nanosilver nucleation and growth sites) on the surface or edge of graphene; controls the active positions and amounts of nanosilver nucleation and growth by designing and controlling different oxygen-containing functional groups and their grafting sites and amounts to precisely control the loading mode, loading amount and loading morphology of nanosilver, thereby providing an ideal experimental carrier for studying the relationship between the filler structure and conductive properties of conductive inks; and provides high-performance fillers for the research and development of high-performance conductive inks.

[0006] In the preparation process of the above oxygen-containing conductive carrier, strong acid and strong oxidant are added. For example, graphene is often oxidatively modified using concentrated sulfuric acid and potassium permanganate, and carbon black is often oxidatively modified using nitric acid or persulfide. Therefore, the synthesized conductive carrier mixed solution contains a large amount of impurities such as alkali metals and acid anions. Alkali metals will occupy the surface of the conductive carrier, and acid anions will preferentially bind to active metals, making it difficult to bind to the surface of the conductive carrier again, which in turn affects the efficiency of the synthetic loading reaction of the carrier to further load metal active sites; at the same time, the dispersion of graphene and carbon materials in water is greatly affected by pH, so the effective purification of the conductive carrier directly affects the loading of active components and the catalytic performance of the catalyst. Most of the existing purification methods use hydrochloric acid solution for multiple centrifugal washing to remove impurities such as metals and acid anions, but the effect is poor. Summary of the invention

[0007] In view of this, the present invention provides a method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide. Compared with the existing method for purifying a conductive carrier, the method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention can obtain a conductive carrier with an ultra-low impurity content, thereby effectively improving the loading effect of the active components.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide comprises the following steps:

[0010] The crude conductive carrier prepared by the liquid phase oxidation method is placed in a dialysis bag, dialyzed in deionized water, and dried to obtain the conductive carrier for electrocatalytic reduction of carbon dioxide.

[0011] Optionally, in the method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, during the dialysis process, deionized water is replaced 1-2 times a day until the pH of the deionized water is neutral, at which time the conductive carrier in the dialysis bag is in a colloidal state.

[0012] Optionally, in the method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, during the dialysis process, the liquid level of the retained liquid in the dialysis bag containing the crude conductive carrier is kept lower than the liquid level of the exudate, that is, the dialysis bag containing the crude conductive carrier is kept completely immersed in the retained liquid. Since the dialysis bag can only be used in a tied and completely immersed manner, dialysis is performed using concentration differences.

[0013] Optionally, in the purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, before placing the crude conductive carrier in a dialysis bag, it also includes the step of washing the crude conductive carrier with a hydrochloric acid solution, and placing the washing solution and the crude conductive carrier in the dialysis bag together; the concentration of the hydrochloric acid solution is 1-1.7 mol / L. When the concentration of the hydrochloric acid solution is lower than 1 mol / L, the conductive carrier becomes colloidal, the dialysis effect is poor, and the metal ions and anions therein cannot be effectively separated. When the concentration of the hydrochloric acid solution is higher than 1.7 mol / L, a large amount of Cl - , the subsequent dialysis time in the dialysis bag needs to be extended to achieve the corresponding effect.

[0014] Optionally, in the method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, during the hydrochloric acid washing process, fresh dilute hydrochloric acid solution is repeatedly replaced until there is no obvious precipitation phenomenon in the titration of the washing solution, and it can be considered that the metal ion content in the deionized water is close to zero. The number of hydrochloric acid washings recommended by the present invention is 2-5 times, which can be adjusted according to actual conditions.

[0015] Optionally, in the method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, the conductive carrier is selected from oxidized graphite or oxidized modified carbon black.

[0016] Optionally, in the method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, the oxidant used in the liquid-phase oxidation method is selected from oxidizing metal compounds and / or oxidizing inorganic acids.

[0017] Optionally, in the method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, the oxidizing metal compound is selected from at least one of potassium permanganate, potassium chlorate, metal persulfate (such as potassium persulfate, etc.), etc.;

[0018] The inorganic acid having oxidizing property is selected from at least one of concentrated sulfuric acid, nitric acid and perchloric acid.

[0019] In the purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, the specific method used for preparing graphite oxide by liquid phase oxidation of graphite is not limited, and any conventional method in the industry can be used, such as Hummers method, Brodie method, improved Hummers method, improved Staudenmaier method based on Brodie method, etc. As long as oxidizing substances are used in the preparation process, the system containing graphite oxide after the reaction is completed can be treated by dialyzing with deionized water in a dialysis bag.

[0020] In the purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, the carbon black material is oxidatively modified by liquid phase oxidation to prepare oxidatively modified carbon black. The specific method used is not limited, and any conventional method in the industry can be used, such as oxidatively modifying the carbon black under the condition of mainly oxidants such as sulfuric acid, nitric acid and perchloric acid (the reaction temperature is mostly room temperature). After oxidative modification, the surface oxygen-containing groups of the carbon black increase, the specific surface area increases, and the dispersibility is improved.

[0021] Optionally, in the purification method of a conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, the drying is vacuum drying, the temperature of the vacuum drying is ≤70°C, the specific drying time is not limited, and complete drying can be achieved. The present invention recommends a drying time of 6-10h.

[0022] The present invention also provides a conductive carrier for electrocatalytic reduction of carbon dioxide, which is obtained by the above-mentioned purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide. The conductive carrier obtained by the purification method has the remarkable characteristics of low metal impurity content and is easy to complex with other active metal components.

[0023] The present invention also provides a catalyst for electrocatalytic reduction of carbon dioxide, comprising a conductive carrier and an active component, wherein the conductive carrier is obtained by the above-mentioned purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide.

[0024] Optionally, in the catalyst for the electrocatalytic reduction of carbon dioxide provided by the present invention, the specific active component can be determined according to the target product. For example, when used for the electrocatalytic reduction of carbon dioxide to prepare formic acid or carbon monoxide, tin oxide or the like can be used as the active component; if used for the electrocatalytic reduction of carbon dioxide to achieve carbon-carbon coupling, metallic copper can be used as the active component.

[0025] When the catalyst for electrocatalytic reduction of carbon dioxide is used to achieve carbon-carbon coupling, the active component includes copper, and the content of copper is 1%-65% based on 100% of the mass of the catalyst for electrocatalytic reduction of carbon dioxide.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] Beneficial effect 1: The purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention, the crude conductive carrier obtained by liquid phase oxidation method is placed in a dialysis bag, and dialyzed in deionized water, through the concentration difference, on the one hand, the metal salt ions electrostatically adsorbed by the carboxyl / hydroxyl groups on the surface of the oxidized carbon material (such as oxidized graphite, oxidized carbon black, etc.) are effectively removed, and the carboxyl / hydroxyl adsorption sites on the surface of the oxidized modified carbon material are released. On the other hand, the free acid radical ions are removed, and the preferential coordination adsorption of the acid radical ions to the metal ions during metal loading is avoided. When the conductive carrier obtained by the purification method provided by the present invention is further prepared into a metal-loaded catalyst, it can significantly improve the binding effect of the metal ions in the metal impregnation solution and the carboxyl / hydroxyl groups on the surface of the oxidized modified carbon material, and avoid the electromagnetic shielding caused by the salt ions in the carrier solution during the further hydrothermal loading of metal nanoparticles on the carrier, thereby improving the metal coverage of the carrier loading.

[0028] Beneficial effect 2: In the preparation process of existing oxidized carbon materials, metal salts or inorganic acids with strong oxidizing properties are often used to treat the surface of the conductive carbon materials. Therefore, the obtained conductive carrier dispersion often contains a large amount of metal ions and anions, which cause electromagnetic shielding for the subsequent target metal loading, resulting in only a small number of metal active sites on the carrier, which in turn leads to a low loading rate of active metals. In the prior art, the conductive carbon material is generally first centrifuged in a hydrochloric acid solution, and then placed in water for centrifugation. When centrifuged in water, due to the neutral environment, the conductive carbon material will become colloidal, making the centrifugation process difficult to carry out. Moreover, the use of hydrochloric acid solution and water to remove metal ions and anions in the crude product is less effective.

[0029] The conductive carrier prepared by the purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide provided by the present invention creatively uses a dialysis bag to dialyze the crude conductive carrier, and after removing the metal salt and anion on the surface of the conductive carrier, the conductive carrier finally obtained not only has a large specific surface area, but also can load more metal active sites, and can also provide a higher electronic conduction efficiency, and reduce the conduction resistance at the electrode-electrolyte interface; when the catalyst is subsequently prepared, it is easy to load metal nanoparticles, especially copper-based nanoparticles, to obtain an electrode catalyst for electrolytic reduction of carbon dioxide to ethylene. The whole process is simple, convenient, and easy to operate.

[0030] Beneficial effect 3: The method for purifying a conductive carrier for the electrocatalytic reduction of carbon dioxide provided by the present invention can further improve the removal effect of metal ions and anions in the crude conductive carrier by further repeatedly washing the metal ions remaining on the surface of the oxidized carbon material with a hydrochloric acid solution of a specific concentration, and then putting the washed oxidized modified carbon material and the washing solution into a dialysis bag, and dialyzing with deionized water. At the same time, the dialysis time can be shortened. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a transmission electron microscope image of graphite oxide obtained in Example 1 of the present invention;

[0032] Figure 2 This is a transmission electron micrograph of the highly dispersed metal loaded on the graphite oxide carrier obtained in Example 1 (5Cu@rGO). DETAILED DESCRIPTION

[0033] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0034] If no specific experimental steps or conditions are specified in the examples and comparative examples, the conventional experimental steps or conditions described in the literature in the art can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be purchased commercially.

[0035] Source of raw materials or equipment: (including raw material name, specifications, manufacturer, etc.)

[0036] Graphite powder, AR, >99.85%, Sinopharm Chemical Reagent Co., Ltd.; Potassium persulfate, AR, >99.5%, Sinopharm Chemical Reagent Co., Ltd.; Phosphorus pentoxide, AR, >98%, Sinopharm Chemical Reagent Co., Ltd.; Concentrated sulfuric acid, AR, 95%-98%, Xilong Chemical Co., Ltd.; Sodium nitrate, AR, >99%, Xilong Chemical Co., Ltd.; Potassium permanganate, AR, >99%, Sinopharm Chemical Reagent Co., Ltd.; 30% hydrogen peroxide, AR, >85%, Xilong Chemical Co., Ltd.; Hydrochloric acid, AR, 36%-38%, Xilong Chemical Co., Ltd.; Potassium chlorate, AR, >99.5%, Xilong Chemical Co., Ltd.; Copper nitrate trihydrate, AR, 99.0~102.0%, Sinopharm Chemical Reagent Co., Ltd.; Hydrazine hydrate, AR, ≥85.0%, Sinopharm Chemical Reagent Co., Ltd. Carbon black (carbon black), >99.5%, 100nm, Shanghai MacLean Biochemical Technology Co., Ltd.

[0037] Example 1

[0038] This embodiment provides a method for preparing graphite oxide (GO) using an improved Hummers method, and the specific steps are as follows:

[0039] Oxidation: Under stirring conditions, add 20g of graphite powder, 10g of K2S2O8 and 10g of P2O5 to 30mL of 80℃ concentrated sulfuric acid in sequence, react for 5h, and add 1500mL of H2O to dilute the mixture after it cools to room temperature, then filter and wash until the filtrate is neutral, and dry it at room temperature for one day to obtain pre-oxidized graphite. Under continuous stirring and ice bath conditions, add 10g of pre-oxidized graphite and 5g of NaNO3 to 230mL of concentrated H2SO4 precooled to 0℃, and then add 30g of KMnO4 in small amounts and multiple times so that the reaction temperature does not exceed 20℃, then remove the ice bath, and continue to react for 2h when the temperature rises to 35℃, then add 460mL of H2O to dilute, and after 15min, add 1400mL of hot H2O to dilute, and at the same time, in order to neutralize the unreacted KMnO4, add 25mL of hydrogen peroxide (30%); finally, filter the mixture to obtain crude graphite oxide;

[0040] Post-treatment: The crude graphite oxide was repeatedly filtered and washed with 1.09 mol / L HCl solution to remove most of the residual metal ions and acid ions until there was no obvious precipitation titration in the washing liquid. The washed crude graphite oxide solution was placed in a dialysis bag and dialyzed with deionized water (keeping the liquid level of the retained liquid in the dialysis bag lower than the liquid level of the exudate), changing the water once a day until the pH of the deionized water was neutral (5 days), and then vacuum dried at 50°C for 8 h to obtain graphite oxide (GO).

[0041] Comparative Example 1

[0042] The preparation method of graphite oxide provided in this comparative example is similar to that in Example 1, except that the post-treatment is different. The post-treatment method used in this comparative example is as follows:

[0043] The crude graphite oxide was evenly distributed in 10 mL centrifuge tubes, 8 mL of 1.09 mol / L HCl solution was added to each centrifuge tube, the tubes were shaken repeatedly, and the mixture was centrifuged at 10000 r / min for 10 min. The crude graphite oxide in each centrifuge tube was washed and centrifuged three times with the HCl solution, then replaced with deionized water, and washed and centrifuged three times (the graphite oxide was colloid-like in this process, and the centrifugation process was more difficult, but centrifugation could be achieved), and then dried under vacuum at 50 ° C for 8 h to obtain graphite oxide.

[0044] Comparative Example 1-1

[0045] The preparation method of graphite oxide provided in this comparative example is similar to that in Example 1, except that the post-treatment step is omitted in this comparative example, and the crude graphite oxide is directly dried at 50° C. in vacuum for 8 h to obtain graphite oxide. The graphite oxide contains a large amount of metals and impurity ions.

[0046] Example 2

[0047] This embodiment provides a method for preparing graphite oxide by using the Brodie method and concentrated HNO3 and KClO3 as an oxidation system, which specifically includes the following steps:

[0048] Oxidation: 5 g of graphite and 5 g of KClO3 were uniformly mixed, and then 20 mL of concentrated HNO3 was added, and the whole system was reacted in a 60 ° C bath for 3.5 days. Then the reactant was washed with water several times and filtered to obtain crude graphite oxide.

[0049] Post-treatment: The crude graphite oxide was repeatedly washed with 1.3 mol / L HCl solution to remove most of the residual metal ions and acid ions until there was no obvious precipitation titration in the washing solution. The washed solution containing graphite oxide was placed in a dialysis bag and dialyzed with deionized water (keeping the liquid level of the retained liquid in the dialysis bag lower than the liquid level of the exudate). The water was changed once a day until the pH of the deionized water was neutral (6 days), and then vacuum dried at 60°C for 7 hours to obtain graphite oxide (GO).

[0050] Comparative Example 2

[0051] The preparation method of graphite oxide provided in this comparative example is similar to that in Example 2, except that the post-treatment is different. The post-treatment method used in this comparative example is as follows:

[0052] The crude graphite oxide was evenly distributed in 10 mL centrifuge tubes, 8 mL of 1.09 mol / L HCl solution was added to each centrifuge tube, the tubes were shaken repeatedly, and the mixture was centrifuged at 10000 r / min for 10 min. The crude graphite oxide in each centrifuge tube was washed and centrifuged three times with the HCl solution, and then replaced with deionized water, and washed and centrifuged three times (the graphite oxide was colloid-like in this process, and the centrifugation process was more difficult, but centrifugation could be achieved), and then dried under vacuum at 60 ° C for 7 h to obtain graphite oxide.

[0053] Example 3

[0054] This embodiment provides a method for preparing GO by using an improved Staudenmaier method based on the Brodie method, that is, adding a certain amount of concentrated H2SO4 to the original HNO3 and KClO3 oxidation system. The specific experimental process is as follows:

[0055] Oxidation: First, 14 mL of concentrated H2SO4 and 6 mL of concentrated HNO3 solution were uniformly mixed, and graphite was slowly added to the mixed solution; then, 5 g of KClO3 was slowly added to the mixed reactants, and the reaction was continued at room temperature for 4 days, and then the reactants were washed with water and filtered to obtain GO crude product;

[0056] Post-treatment: The crude GO product was repeatedly filtered and washed with 1.6 mol / L HCl solution to remove most of the residual metal ions and acid ions until there was no obvious precipitation titration in the washing liquid. The washed solution containing graphite oxide was placed in a dialysis bag and dialyzed with deionized water (keeping the liquid level of the retained liquid in the dialysis bag lower than the liquid level of the exudate). The water was changed twice a day until the pH of the deionized water was neutral (7 days), and then vacuum dried at 50°C for 8 h to obtain graphite oxide (GO).

[0057] Comparative Example 3

[0058] The preparation method of graphite oxide provided in this comparative example is similar to that in Example 3, except that the post-treatment is different. The post-treatment method used in this comparative example is as follows:

[0059] The crude graphite oxide was evenly distributed in 10 mL centrifuge tubes, 8 mL of 1.09 mol / L HCl solution was added to each centrifuge tube, the tubes were shaken repeatedly, and the mixture was centrifuged at 10000 r / min for 10 min. The crude graphite oxide in each centrifuge tube was washed and centrifuged three times with the HCl solution, then replaced with deionized water, and washed and centrifuged three times (the graphite oxide was colloid-like in this process, and the centrifugation process was more difficult, but centrifugation could be achieved), and then dried under vacuum at 50 ° C for 8 h to obtain graphite oxide.

[0060] Example 4

[0061] The preparation method of graphite oxide provided in this example is similar to that in Example 1, except that the post-treatment is different. The post-treatment method used in this comparative example is as follows:

[0062] Post-treatment: The crude graphite oxide was placed in a dialysis bag and dialyzed with deionized water (keeping the liquid level of the retained liquid in the dialysis bag lower than the liquid level of the exudate), changing the water twice a day until the pH of the deionized water was neutral (5 days), and then vacuum dried at 50°C for 8 h to obtain graphite oxide (GO).

[0063] Comparative Example 4

[0064] The preparation method of graphite oxide provided in this example is similar to that in Example 1, except that the post-treatment is different. The post-treatment method used in this comparative example is as follows:

[0065] Post-treatment: The crude graphite oxide was evenly distributed in 10 mL centrifuge tubes, 8 mL of deionized water was added to each centrifuge tube, the tubes were shaken repeatedly, and centrifuged at a rate of 10000 r / min for 10 min. The crude graphite oxide in each centrifuge tube was washed repeatedly with deionized water and centrifuged three times (the graphite oxide was colloid-like in this process, and the centrifugation process was more difficult, but centrifugation could be achieved), and then vacuum dried at 50 ° C for 8 h to obtain graphite oxide.

[0066] Example 5

[0067] This embodiment provides a method for liquid phase oxidation modification of carbon black, which specifically comprises the following steps:

[0068] Oxidation: Add 100 mL of 30% acidic potassium permanganate solution (formed by mixing hydrochloric acid and potassium permanganate, with a mass content of potassium permanganate of 30%) and 10 g of carbon black into a beaker, stir magnetically at room temperature for 3 h, and filter after the reaction to obtain a crude oxidized modified carbon black;

[0069] Modification: The crude oxidized carbon black was repeatedly washed with 1.09 mol / L HCl solution to remove most of the residual metal ions and acid ions until there was no obvious precipitation titration in the washing liquid. The washed solution was placed in a dialysis bag and dialyzed with deionized water (keeping the liquid level of the retained liquid in the dialysis bag lower than the liquid level of the exudate). The water was changed twice a day until the pH of the deionized water was neutral (5 days), and then vacuum dried at 50°C for 8 h to obtain an oxidized modified carbon black material.

[0070] Comparative Example 5

[0071] The preparation method of the oxidatively modified carbon black provided in this comparative example is similar to that of Example 5, except that the post-treatment is different. The post-treatment method used in this comparative example is as follows:

[0072] The crude oxidized carbon black was evenly distributed in 10 mL centrifuge tubes, 8 mL of 1.09 mol / L HCl solution was added to each centrifuge tube, the tubes were shaken repeatedly, and the mixture was centrifuged at 10000 r / min for 10 min. The crude oxidized graphite in each centrifuge tube was washed and centrifuged three times with the HCl solution, then replaced with deionized water, and washed and centrifuged three times (the carbon black was oxidized into a colloidal state in this process, and the centrifugation process was more difficult, but centrifugation could be achieved), and then dried under vacuum at 50 ° C for 8 h to obtain oxidized modified carbon black.

[0073] The GO / oxidation-modified carbon black material prepared in the above-mentioned embodiments and comparative examples was used as a conductive carrier, and then a catalyst for electrocatalytic reduction of carbon dioxide was prepared in the following manner:

[0074] (1) Preparation of dispersion: Take 200 mg of dry GO / oxidation-modified carbon black material and add it to 90 mL of deionized water. Ultrasonic disperse it until it is uniform. Transfer the mixed solution to a 100 mL volumetric flask and make up the volume to 100 mL with deionized water. The concentration of the obtained GO / oxidation-modified carbon black material solution is 2 mg / mL. Shake well for use.

[0075] (2) Preparation of copper precursor solution: Weigh 3.802 g of copper nitrate trihydrate and add it to 9.15 g of deionized water. After fully dissolving, a dark blue copper nitrate solution (Cu 2+ Concentration: 100 mg / mL).

[0076] (3) A series of xCu@rGO (x = 5%) electrocatalysts were prepared by in-situ impregnation reduction method. The specific operation is as follows: 50 μL of the above copper nitrate solution was added to 50 mL of GO / oxidized carbon black material solution, heated to 60 ° C and stirred for 8 h, and then 0.5 mL of hydrazine hydrate (85%) was added dropwise to the reaction solution, and the stirring was continued at 60 ° C for 2 h.

[0077] (4) Catalyst washing: The dispersion obtained in step (3) was filtered, and then washed with deionized water and ethanol for more than three times. Finally, the wet solid sample was dried in a vacuum drying oven at 80° C. for 12 h. The obtained catalyst was labeled as 5Cu@rGo / oxidation-modified carbon black material.

[0078] The catalysts prepared by the above method were analyzed by ESCALAB 250Xi X-ray photoelectron spectrometer (Thermo Fisher Scientific, USA, instrument parameters: ① energy scanning range: 1-1400eV; ② optimal energy resolution: ≤0.45eV; ③ optimal sensitivity: 1,000,000cps (Mono XPS, Ag standard 3d5 / 2 peak); ④ optimal vacuum degree of the analysis chamber: better than 3×10-9 mbar) were used to quantitatively analyze the surface elements and the effect of residual ions on the metal loading. The analysis results are shown in the following table.

[0079] Table 1

[0080]

[0081]

[0082] From the data in the above table, it can be seen that by using the same concentration and amount of Cu precursor, using the same impregnation loading steps (i.e., using the same conditions to prepare the catalyst), a higher metal loading can be obtained by using the dialysis-treated GO / oxidation-modified carbon black material carrier with a difference in ion concentration. This shows that the crude GO / carbon black material obtained by oxidation in the present invention can effectively strip off and remove the impurity ions bound to the hydroxyl or carboxyl groups on the surface of the GO / carbon black material after dialyzing with a dialysis bag, which can not only obtain lower ion residues, but also release the active groups on its surface, thereby increasing the active site loading rate when preparing the catalyst by subsequent impregnation loading, and providing favorable conditions for the loading of active metals. However, for the GO / carbon black material that has not been dialyzed, since a metal salt with strong oxidizing properties is used to oxidize the graphite during the preparation process, this treatment method ultimately results in electrostatically adsorbed metal cations on the carboxyl or hydroxyl groups on the surface of the obtained GO / carbon black material, affecting the subsequent metal loading effect.

[0083] Figure 1 is a transmission electron micrograph of graphite oxide (GO) obtained after dialysis treatment in Example 1 of the present invention, Figure 2 for Figure 1 Transmission electron microscopy image of the catalyst obtained by loading 5% copper on graphite oxide (GO). Figure 1 and Figure 2 By comparison, it can be seen that the carrier treated by the purification method provided by the present invention is obviously highly dispersed after loading the metal and has no agglomeration.

[0084] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A method for purifying a conductive carrier for electrocatalytic reduction of carbon dioxide, characterized in that: The steps include: The crude conductive carrier prepared by the liquid phase oxidation method is placed in a dialysis bag, dialyzed in deionized water, and dried to obtain the conductive carrier for electrocatalytic reduction of carbon dioxide.

2. The purification method according to claim 1, characterized in that During the dialysis process, the deionized water was replaced 1-2 times a day until the pH of the deionized water was neutral.

3. The purification method according to claim 1, characterized in that During the dialysis process, the liquid level of the retained liquid in the dialysis bag containing the crude conductive carrier is kept lower than the liquid level of the exudate.

4. The purification method according to claim 1, characterized in that Before placing the crude conductive carrier in a dialysis bag, the method further includes washing the crude conductive carrier with a hydrochloric acid solution; the concentration of the hydrochloric acid solution is 1-1.7 mol / L.

5. The purification method according to claim 1, characterized in that The conductive carrier is selected from graphite oxide or oxidized modified carbon black.

6. The purification method according to claim 1, characterized in that The oxidant used in the liquid phase oxidation method is selected from oxidizing metal compounds and / or oxidizing inorganic acids.

7. The preparation method according to claim 6, characterized in that: The oxidizing metal compound is selected from at least one of potassium permanganate, potassium chlorate and metal persulfate; and / or The inorganic acid having oxidizing property is selected from at least one of concentrated sulfuric acid, nitric acid and perchloric acid.

8. The purification method according to claim 1, characterized in that The drying is vacuum drying, and the temperature of the vacuum drying is ≤70°C.

9. A conductive carrier for electrocatalytic reduction of carbon dioxide, characterized in that: Obtained by the purification method of a conductive carrier for electrocatalytic reduction of carbon dioxide according to any one of claims 1 to 8.

10. A supported catalyst for electrocatalytic reduction of carbon dioxide, characterized in that: The invention comprises a conductive carrier and an active component, wherein the conductive carrier is obtained by the purification method of the conductive carrier for electrocatalytic reduction of carbon dioxide according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Preparation method of nitrogen-doped graphene loaded core-shell-shaped copper-carbon composite catalyst for producing formic acid through electro-catalysis of carbon dioxide

    CN111659437A

  • Graphene and nano-silver composite material and preparation method thereof

    CN113563759A

  • Copper oxide nanosheet catalyst, preparation method thereof and application of copper oxide nanosheet catalyst in electrocatalytic reduction of carbon dioxide and carbon monoxide

    CN115490258A

  • Composite catalyst for regulating and controlling selectivity of carbon dioxide electrocatalytic reduction product and application of composite catalyst

    CN115595607A

  • Method for preparing graphene-loaded nano alloy catalyst

    CN102145305A

Cited By

  • Preparation method of electrode catalyst for preparing ethylene through electrochemical reduction of carbon dioxide

    CN120138685A